Capturing the Processes of Our Transformative Learning in a Transdisciplinary Research Course (LEARNing Landscapes, 2015)
Transdisciplinary scholarship has experienced a renaissance in higher education. Yet, little research has captured transformations in students’ viewpoints as they collaborate in transdisciplinary courses to consider solutions to complex societal problems. In this narrative inquiry, I chronicled my doctoral students’ perspectives and my thinking in a Transdisciplinary Research class in which students attempted to unravel the social justice dilemma of escalating economic disparities between rich and poor citizens in the United States. I believe knowledge is socially constructed. Therefore, student collaboration and sharing of their reflective stances were integral to the curriculum.
Keywords: Transdisciplinary; transformation; social justice; narrative; collaboration